The dynamics of food security policy in Cameroon (2008-2019) - Moudio , Joel (American Journal of Public Policy and Administration, 2021)
Purpose: This article intends to examine the improvement in fighting against food insecurity in Cameroon since February 2008, a period marked with so-called hunger riots. In response to this, and in order to reply satisfactorily to this social crisis and the security that predates it, the government set up, at the end of 2008, the national food security programme (NFSP). This programme, which is the site of our empirical investigation, has undergone some vicissitudes and a marked evolution up to now. Methodology: Based on Using participant observation, non-reactive data collection techniques and socio-historical analysis, the article highlights the concept of the food security policy process, which does not escape the enlightening analytical framework of the advocacy coalition framework. It proposes, based on the analysis of the interpenetration of the NFSP by state and others institutional actors, to outline the contours of a category of negotiated and incremental food security policy process. Findings: Therefore to improve the food security policy process, a social division of labour is needed between the decision-making centre - the Inter-ministerial Committee on Food Security (CISA) and the Steering Committee (COPIL) - and the technical expertise centre - the Technical Group on Food Security (GTSA). Unique contribution to theory, practice and policy: The NFSP should play a more synthesizing role between these two centres in terms of the framework for the elaboration of the national food security policy strategy.